Improvement of the KCF Tracking Algorithm through Object Detection - wan Park, Jae; Kim, Sungjoong; Lee, Youngjae; Joe, Inwhee (International Journal of Engineering and Technology, 2018)
When the position of the beam projector is changed, users have to manually adjust the position. In this paper, we propose a system that can automatically correct images. In this process, the KCF (Kernelized Correlation Filter) algorithm is used for tracking the IR (Infrared) markers. We analyze the object tracking failure problem of the KCF and improve the KCF tracking algorithm that solves the problem through object detection.Â Â